2021
DOI: 10.1021/acsami.0c22736
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Efficiency and Minimalist Intracellular Delivery of Macromolecules Mediated by Latent-Photothermal Surfaces

Abstract: Intracellular delivery of exogenous macromolecules by photothermal methods is still not widely employed despite its universal and clear effect on cell membrane rupture. The main causes are the unsatisfactory delivery efficiency, poor cell activity, poor cell harvest, and sophisticated operation; these challenges stem from the difficulty of simply controlling laser hotspots. Here, we constructed latent-photothermal surfaces based on multiwall carbon nanotube-doped poly(dimethyl siloxane), which can deliver carg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Many nanoparticles including organic or inorganic nanoparticles possess extraordinary photothermal or photodynamic characteristics [ 100 , 142 , 143 , 144 ], making light an attractive stimulus to control the gene delivery. Light of various wavelengths has been used in light-controlled nanocarriers, including ultraviolet light [ 145 ], visible light [ 146 , 147 ] and near-infrared (NIR) light [ 148 ].…”
Section: Stimulus-responsive Nanocarriersmentioning
confidence: 99%
“…Many nanoparticles including organic or inorganic nanoparticles possess extraordinary photothermal or photodynamic characteristics [ 100 , 142 , 143 , 144 ], making light an attractive stimulus to control the gene delivery. Light of various wavelengths has been used in light-controlled nanocarriers, including ultraviolet light [ 145 ], visible light [ 146 , 147 ] and near-infrared (NIR) light [ 148 ].…”
Section: Stimulus-responsive Nanocarriersmentioning
confidence: 99%
“…[18,19,22] Recent studies have shown that photothermal methods have an excellent membrane rupture efficiency, and can promote exosome secretion by heat. [23][24][25][26][27] The above advantages suggest that the photothermal method has a high potential in intracellular delivery in vitro/vivo in a nondestructive and highly efficient manner. However, compared to electroporation, the photothermal method is difficult to drive the directional transmission of exogenous molecules, which limits the intracellular delivery efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Different from carrier-mediated methods, membrane disruption-mediated methods deliver exogenous cargos into cell interior via permeabilization or creation of transient “holes” on the cell membrane by chemical, mechanical, or field-assisted means, providing a nearly universal approach regardless of the properties of delivered cargoes and targeted cells. Of those, photothermal-poration based methods are promising, which involve the transient permeabilization of cell membrane using the heat converted by the photothermal agents (PTAs) from the light (usually near-infrared (NIR) light). For example, gold nanoparticles (GNPs), as efficient PTAs, have been exploited for intracellular delivery. , By attaching GNPs to the cell surface, the photothermal poration effect could be achieved under NIR irradiation, facilitating the entry of external molecules into cytoplasm. Although the GNPs-based technology has shown broad applicability across diverse delivered molecules and cell types, it should be noted that after delivery most of the GNPs remained on the cell surface even after rigorous washing, and some GNPs and their small fragments entered the cells along with the cargos, which might compromise cell viability and cause possible side effects . To solve this limitation, some photothermal electrospun nanofibers were developed by embedding PTAs inside the nanofibers to avoid direct contact between PTAs and cells. , However, harvesting the “engineered” cells nontraumatically and effectively from these nanofibers became a new challenge.…”
Section: Introductionmentioning
confidence: 99%